Inter-relationships between light and respiration in the control of ascorbic acid synthesis and accumulation in Arabidopsis thaliana leaves - Bartoli, Carlos Guillermo (2006)
The effects of growth irradiance and respiration on ascorbic acid (AA) synthesis and accumulation were studied in the leaves of wild-type and transformed Arabidopsis thaliana with modified amounts of the mitochondrial alternative oxidase (AOX) protein. Plants were grown under low (LL; 50 μmol photons m-2 s-1), intermediate (IL; 100 μmol photons m-2 s-1), or high (HL; 250 μmol photons m-2 s-1) light. Increasing growth irradiance progressively elevated leaf AA content and hence the values of dark-induced disappearance of leaf AA, which were 11, 55, and 89 nmol AA lost g-1 fresh weight h-1, from LL-, IL-, and HL-grown leaves, respectively. When HL leaves were supplied with L-galactone-1,4-lactone (L-GalL; the precursor of AA), they accumulated twice as much AA and had double the maximal L-galactone-1,4-lactone dehydrogenase (L-GalLDH) activities of LL leaves. Growth under HL enhanced dehydroascorbate reductase and monodehydroascorbate reductase activities. Leaf respiration rates were highest in the HL leaves, which also had higher amounts of cytochrome c and cytochrome c oxidase (CCO) activities, as well as enhanced capacity of the AOX and CCO electron transport pathways. Leaves of the AOX-overexpressing lines accumulated more AA than wild-type or antisense leaves, particularly at HL. Intact mitochondria from AOX-overexpressing lines had higher AA synthesis capacities than those from the wild-type or antisense lines even though they had similar L-GalLDH activities. AOX antisense lines had more cytochrome c protein than wild-type or AOX-overexpressing lines. It is concluded that regardless of limitations on L-GalL synthesis by regulation of early steps in the AA synthesis pathway, the regulation of L-GalLDH activity via the interaction of light and respiratory controls is a crucial determinant of the overall ability of leaves to produce and accumulate AA.